The long-term outcome after acute kidney injury: a narrative review - Pôncio,Luana (2015)
This review will focus on long-term outcomes after acute kidney injury (AKI). Surviving AKI patients have a higher late mortality compared with those admitted without AKI. Recent studies have claimed that long-term mortality in patients after AKI varied from 15% to 74% and older age, presence of previous co-morbidities, and the incomplete recovery of renal function have been identified as risk factors for reduced survival. AKI is also associated with progression to chronic kidney (CKD) disease and the decline of renal function at hospital discharge and the number and severity of AKI episodes have been associated with progression to CKD. IN the most studies, recovery of renal function is defined as non-dependence on renal replacement therapy which is probably too simplistic and it is expected in 60-70% of survivors by 90 days. Further studies are needed to explore the long-term prognosis of AKI patients.